Coping Strategies and Their Subscales: Correlation with Maternity Blues - Wartisa, Feny; Lestari, Yuniar; Yusrawati, Yusrawati; Yanis, Amel (Andalas Obstetrics And Gynecology Journal, 2025)
Background: Postpartum mothers are susceptible to clinical symptoms of depression. Maternity blues is one of the most common postpartum depressions. Objectives: This research aims to identify the correlation between coping strategies and maternity blues in Bukittinggi City. Methods: This Cross-sectional Study was conducted in Bukittinggi City, West Sumatra, Indonesia, involving 126 postpartum mothers recruited consecutively. Data analysis in this study used the Spearman's Rank correlation test. Results: The results of the study showed that problem-focused coping strategies had a positive correlation with maternity blues (p-value: 0.025; r = 1,000). Emotion-focused coping strategies had a negative correlation with maternity blues (p-value: 0.015; r = -0.216). While the type of Avoidance focused coping strategy has a positive correlation with maternity blues (P Value: 0.000; r = 0.446). Conclusion: Problem-focused and emotional coping strategies have a positive correlation with maternity blues. Avoidance-focused coping strategies have a negative correlation with maternity blues. Keywords: Coping strategies, maternity blues, subscales